Advances in library administration and organization. Vol. 23 - Nyce, James M.; Williams, Delmus Eugene; Garten, Edward D. (Emerald, 2006)
This volume of Advances in Library Administration and Organization is designed to help administrators meet the challenges of running organizations in an ambiguous climate. It leads with a paper that uses innovation theory and a communications model to track how LIS practitioners acquire the theoretical base required to undergird their efforts. This theoretical piece is followed by a very personal view of what knowledge one must acquire to succeed as a leader of libraries, offering a more practical view of how administrators develop. Then comes a set of papers that address very real problems - performance assessment and its impact, the question of whether it is profitable for communities to completely outsource public library operations, and then three separate articles that look at career paths for public and academic librarians and the retention of those people by organizations. On a different tack, another contributor looks at how libraries communicate with their clients while cutting journals to insure consumer confidence in the decision-making process of the library; subsequently developing a model for joint decision-making that should be of interest to our community. The final paper leaves the realm of the library and examines how public and private organizations in the United Kingdom manage information as an asset and how that affects their performance in the marketplace. As in past volume, this edition of ALAO includes an eclectic collection of strong papers that convey the results of kind of research that managers need, mixing theory with a good dose of pragmaticism. The result should add value to the literature. It addresses theoretical and practical issues administrators face in ambiguous environments and presents an eclectic collection of papers that reflect the myriad challenges library administrators face everyday.
Includes indexes.
Keywords: Library administration.; elektronické knihy; electronic books